Nitrogen-Deficiency Stress Induces Protein Expression Differentially in Low-N Tolerant and Low-N Sensitive Maize Genotypes - Nazir, Muslima; Pandey, Renu; Siddiqi, Tariq O.; Ibrahim, Mohamed M.; Qureshi, Mohammad I.; Abraham, Gerard; Vengavasi, Krishnapriya; Ahmad, Altaf (Frontiers in Plant Science, 2016)
Nitrogen (N) is a critical element for plant growth and its application has proven to be a valuable agricultural practice. However, unavoidable economic and environmental problems associated with excessive use of N-fertilizers demands its better management. The solution lies in improving the N use efficiency to sustain productivity even at low N levels. Evaluation of 32 maize genotypes using physiological and biochemical traits under optimum (4.5 mM) and low N (0.5 mM) was carried out. The contrasting low-N sensitive (HM-4) and low-N tolerant (PEHM-2) genotypes were used for comparative proteome-profiling of leaves under optimum and low N as well as restoration of low N on 3rd (NR3) and 5th (NR5) days after re-supplying N. The analysis of differential expression pattern of proteins was performed by 2-D gel electrophoresis. Significant variations in the expression of proteins were observed under low N, which were genotype specific. In the leaf proteome, 25 spots were influenced by N treatment and 4 spots were different between the two genotypes. Most of the proteins that were differentially accumulated in response to N level and were involved in photosynthesis and metabolism, affirming the relationship between N and carbon metabolism. In addition to this, greater intensity of some defense proteins in the low N tolerant genotype was found that may have a possible role in imparting it tolerance under N starvation conditions. The new insights generated on maize proteome in response to N-starvation and restoration would be useful towards improvement of N-use efficiency in maize.